Daptomycin for Treatment of S. Epidermidis Endocarditis in an Extremely Preterm Neonate-Outcome and Perspectives - Chiara Minotti; Ilaria Zuccon; Elena Priante; Luca Bonadies; Costanza Di Chiara; Daniele Donà; Eugenio Baraldi; Paola Costenaro (MDPI AG, 2022)
With a considerable morbidity and mortality burden, infective endocarditis still represents a challenge for clinicians. This is a case of persistent Staphylococcus epidermidis endocarditis in an extremely preterm newborn. The infection, initially treated with vancomycin, was successfully cured with daptomycin. Its use was safe and effective, ensuring a complete remission without adverse effects.